Leonardesmus injucundus, n. gen., n. sp., an aromatic, small-bodied milliped from Washington State, U. S. A., and a revised account of the family Nearctodesmidae (Polydesmida) - Shelley, Rowland M.; Shear, William A. (Zootaxa, 2006)
Leonardesmus injucundus, the first small-bodied, "micro-nearctodesmid," from north of the southwestern states, is proposed for a litter and soil-dwelling milliped in Washington state that emits an unusually strong, pungent defensive secretion; the aroma is often detected before the milliped is actually seen. Harpogonopus Loomis, 1960, occurring along the coast of southern California and Baja California Norté, is confirmed for the Nearctodesmidae, and three southwestern "micro-nearctodesmid" genera—Tidesmus Chamberlin, 1943, and Phreatodesmus and Oodedesmus, both by Loomis, 1960—are placed here tentatively. The Nearctodesmidae is formally recorded from the area of Harpogonopus and scattered sites in the deserts and inselbergs of southern California, Arizona, and Nevada. SEM photos of somatic and gonopodal features are provided in addition to line drawings of the latter; the photos reveal details that are invisible under light microscopy, but they mask a translucent surface lamina that is revealed by the latter. The two techniques therefore complement each other, and diplopodologists are cautioned against exclusive reliance on SEM. Thin, closely appressed laminae exist in many diplopod families, and SEM may erroneously show them as a single structure.